Targeting need: a methodological review of a socioeconomic urban regeneration initiative in Belfast - McKibben, Tony (Statistical and Social Inquiry Society of Ireland, 2000)
The problems of social exclusion currently occupy centre stage in the thinking of government in both the United Kingdom and the Republic of Ireland. Considerable efforts are being made to assess the extent of the problem and to formulate strategies to deal with it. While the present degree of activity might suggest to many that this is a newly discovered phenomenon, that is far from being the case. The problem of social exclusion, poverty, relative or multiple disadvantage - there are many and no agreed definition as to social exclusion (Hills, 1999) - is one which government in Northern Ireland have tried to alleviate for a considerable period of time. A particular challenge is ensuring that resources are targeted at those who are most in need. Drawing on the experiences of the Making Belfast Work (MBW) initiative this paper reviews the methodologies employed to identify and tackle deprivation within Belfast and illustrate how the lessons learnt will guide future intervention in this field. It will describe the methodologies used in both the targeting of the problem as well as the assessment of impact and the implication for future data requirements in the context of the New Targeting Social Need (New TSN) polic
Read before the Society, 6 April 2000
Keywords: Social exclusion - Northern Ireland; Belfast; Urban regeneration; 314.15